SHORT-TERM DEBT, PROFITABILITY AND STOCK MARKET VOLATILITY AT THE NAIROBI SECURITIES EXCHANGE, KENYA - Vivyanne Omira; Isaac Linus Ochieng; Gordon Opuodho (ZILLZELL MEDIA PRIMA, 2025)
This study examines the relationship between short-term debt and stock market volatility among firms listed on the Nairobi Securities Exchange (NSE) in Kenya. Acknowledging the increased sensitivity of emerging markets to external financial shocks, the research aims to clarify how short-term financing affects market dynamics. Using secondary data from the NSE and company financial reports covering the period from 2013 to 2022, the study employs a quantitative approach that incorporates multiple linear regression, Pearson correlation analysis, and panel random effects models to capture both cross-sectional and time-series variations. The findings reveal a cyclical pattern in short-term borrowing and a strong positive relationship between short-term debt and market volatility. Regression analysis, which considers firm size and profitability, further confirms that short-term debt has a statistically significant positive impact on volatility. This suggests that short-term financing contributes to market instability when firm-specific factors are taken into account. The persistent presence of short-term debt in corporate capital structures underscores its strategic importance. These results highlight the need for investors and policymakers to carefully monitor corporate debt profiles to mitigate volatility risks in emerging financial markets.